2024
DOI: 10.1111/srt.13627
|View full text |Cite
|
Sign up to set email alerts
|

Skin boosters: Definitions and varied classifications

Kyu‐Ho Yi,
Waranaree Winayanuwattikun,
Sung‐Yeon Kim
et al.

Abstract: BackgroundThe concept of “skin boosters” has evolved, marking a shift from traditional uses of hyaluronic acid (HA) fillers primarily for augmenting skin volume to a more diverse application aimed at improving dermal conditions. Restylane Vital and other HA fillers have been repurposed to combat skin aging and wrinkles by delivering HA directly to the dermis.ObjectivesThis review aims to define the term “skin booster” and to discuss the various components that constitute skin boosters. It seeks to provide a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…Clinical trials have demonstrated that PRP can improve skin texture, tone, and elasticity, while also reducing the appearance of wrinkles, fine lines, and pigmentation changes. 5,39 PRP can be prepared by either a one or two-step centrifugation process that concentrates platelets from the patient's blood. However, factors such as centrifugation speed, time, and temperature, as well as the use of different anticoagulants, can affect the final composition of PRP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials have demonstrated that PRP can improve skin texture, tone, and elasticity, while also reducing the appearance of wrinkles, fine lines, and pigmentation changes. 5,39 PRP can be prepared by either a one or two-step centrifugation process that concentrates platelets from the patient's blood. However, factors such as centrifugation speed, time, and temperature, as well as the use of different anticoagulants, can affect the final composition of PRP.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have demonstrated that PRP can improve skin texture, tone, and elasticity, while also reducing the appearance of wrinkles, fine lines, and pigmentation changes. 5 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a significant challenge remains as natural penetration without mechanical assistance is difficult. 1 To address this, gold PTT using ethosomes has been developed, representing a new generation of PTT that surpasses previous limitations and demonstrates its efficacy. Ethosomes, advanced lipid-based nanosystems, consist of phospholipids and ethanol.…”
Section: What Is Ethosome Photothermal Therapy?mentioning
confidence: 99%
“…Nevertheless, a significant challenge remains as natural penetration without mechanical assistance is difficult. 1 …”
mentioning
confidence: 99%
“…The field of aesthetic medicine has witnessed a significant increase in the utilization of biostimulatory materials, including Polylactic Acid (PLLA), Calcium Hydroxylapatite (CaHA), Polydioxanone (PDO), Hyaluronic Acid (HA), Polydeoxyribonucleotide (PDRN), and Polynucleotide (PN). 1 These materials come in various forms, ranging from absorbable threads that can be strategically inserted into the skin to powder forms that are reconstituted and injected as a liquid or gel directly into target areas. Absorbable threads, owing to their physical properties, can exert tensile forces on tissues, imparting a lifting effect and enhancing structural strength until they gradually dissolve.…”
Section: Introductionmentioning
confidence: 99%